Corrosion behaviour of Al/SiC and Al/Al2O3 nanocomposites - Tamer Samir Mahmoud (Materials Research, 2012)
In the present investigation, the static immersion corrosion behavior of Al/Al2O3 and Al/SiC nanocomposites in 1 M HCl acidic solution was evaluated. The nanocomposites were fabricated using conventional powder metallurgy (P/M) route. The effect of nanoparticulates size and volume fraction on the corrosion behavior of nanocomposites was studied. The durations of the corrosion tests ranged from 24 to 120 hours and the temperatures of the solution ranged from ambient to 75 ºC. The corrosion rates of the nanocomposites were calculated using the weight loss method. The results showed that both Al/SiC and Al/Al2O3 MMNCs have lower corrosion rates than the pure Al matrix. Such behavior was noticed at both ambient and higher temperatures. Generally, the Al/Al2O3 nanocomposites exhibited lower corrosion rates than the Al/SiC nanocomposites. The Al/Al2O3 (60 nm) nanocomposites exhibited the highest corrosion resistance among all the investigated nanocomposites. The corrosion rate was found to be reduced by increasing of the exposure time and the volume fraction of the nanoparticulates, while it was found to be increased by increasing of the nanoparticulates size and the solution temperature.